Cranial Nerve VI Palsy After Dural-Arachnoid Puncture. (March 2015) - Hofer, Jennifer E.; Scavone, Barbara M.
<x xml:space="preserve">Abstract</x> In this article, we provide a literature review of cranial nerve (CN) VI injury after dural-arachnoid puncture. CN VI injury is rare and ranges in severity from diplopia to complete lateral rectus palsy with deviated gaze. The proposed mechanism of injury is cerebrospinal fluid leakage causing intracranial hypotension and downward displacement of the brainstem. This results in traction on CN VI leading to stretch and neural demyelination. Symptoms may present 1 day to 3 weeks after dural-arachnoid puncture and typically are associated with a postdural puncture (spinal) headache. Resolution of symptoms may take weeks to months. Use of small-gauge, noncutting spinal needles may decrease the risk of intracranial hypotension and subsequent CN VI injury. When ocular symptoms are present, early administration of an epidural blood patch may decrease morbidity or prevent progression of ocular symptoms.